The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/tan.12279
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐class II alleles in patients with drug‐resistant pulmonary tuberculosis in Kazakhstan

Abstract: The human leukocyte antigen (HLA) system has a major role in the regulation of the immune response as it is involved in the defense against pathogens. Some studies have reported that HLA class II genes play a strong role in severe cases of pulmonary tuberculosis (PTB) in several populations. Thus the aim of the study was to compare the HLA-class II alleles of patients with drug resistant tuberculosis with those of healthy controls from the same ethnic group in Kazakhstan. The aim of the present study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…For example, DRB1*15 has been reported to be associated with the susceptibility of TB in various ethnic groups such as Indian (Rajalingam et al, 1996;Ravikumar et al, 1999;Stroup DF et al, 2000;Sriram et al, 2001;Mishra et al, 2014;Kuranov et al, 2014), Mexican (Teran et al, 1999), Chinese (Shi et al, 2011), Polish (Dubaniewicz et al, 2005) and Korean (Kim et al, 2005). DRB1*16 is reported to have a positive association with the susceptibility to tuberculosis in Polish population (Dubaniewicz et al, 2005), but a negative association in the Sahariya tribe of North Central India (Mishra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DRB1*15 has been reported to be associated with the susceptibility of TB in various ethnic groups such as Indian (Rajalingam et al, 1996;Ravikumar et al, 1999;Stroup DF et al, 2000;Sriram et al, 2001;Mishra et al, 2014;Kuranov et al, 2014), Mexican (Teran et al, 1999), Chinese (Shi et al, 2011), Polish (Dubaniewicz et al, 2005) and Korean (Kim et al, 2005). DRB1*16 is reported to have a positive association with the susceptibility to tuberculosis in Polish population (Dubaniewicz et al, 2005), but a negative association in the Sahariya tribe of North Central India (Mishra et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified a positive association between the DRB1 alleles and TB across geographical locations-DRB1*15 in the Sahariya tribe (Mishra et al, 2014), DRB1*0801 and DRB1*0803 in Kazakhstan (Kuranov et al, 2014), DRB1*15 in Chinese (Shi et al, 2011), DRB1*14 in Portuguese (Duarte et al, 2011), DRB1*0803 in Korean (Kim et al, 2005), DRB1*16 in Polish (Dubaniewicz et al, 2000), DRB1*04 and DRB1*11 in Syrian (Harfouch and Daher, 2008), and DRB1*07 in Iranian populations (Amirzargar et al, 2004). However, other studies have reported no association.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility to tuberculosis is controlled genetically in different populations. The DRB1*08:03 allele may be associated with tuberculosis progression and may affect the development of drug resistance and recurrent disease in Kazakhs [6]. Although the clinical diagnosis of SCID was the primary reason for the clinical course, genetic factors also may have contributed to the poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine articles were excluded after acquiring and reading the full text in detail (five studies with duplicate/overlapping articles, four studies without data of interest or raw data, six studies that were reviews, two articles in Russian language, and 32 studies that were about HLA-DRB1). In the end, a total of 12 studies were available for this meta-analysis, among which, all of them were about DQB1 [2,[10][11][12][13][19][20][21][22][23][24][25], and 6 studies were about DQA1 [10,13,19,21,24,25].…”
Section: Quality Assessmentmentioning
confidence: 99%